Augmented reality guided condylectomy. Issue 7 (September 2022) - Bussink, Thijs; Maal, Thomas; Meulstee, Jene; Xi, Tong
Abstract: An accurate transfer of a 3D virtual planned proportional condylectomy to the patient is challenging due to the limited surgical access. A new clinical workflow that uses augmented reality to assist a condylectomy is presented step-by-step. This AR-based approach has the potential to be implemented in the clinical setting routinely.